From an Embodied Understanding to Ethical Considerations during Creative Practice - Falin , Priska; Falin, Petra; Mäkelä, Maarit (FormAkademisk, 2023)
This paper discusses material-based creative processes in the context of higher education. The focus is on the ethical aspects related to material considerations during the iterative phases of personal projects. We explore how personal feelings and an embodied understanding of the material world influence decisions on how and why we engage with different materials during creative processes. Recent trends in material-based research aim to explore the relationships between humans and materials, examining them as equal members in research and thus challenging the top-down perception of materials as mere resources for human needs. However, this kind of approach to research and material-based creative practices requires ethical considerations that reach not only the human but also the non-human world. In this paper, we open this discussion by examining design students’ creative processes, which unfold an understanding of ethics in relation to non-humans. We build on data consisting of documentation, reflections and outcomes derived from the creative processes of four MA-level students and discuss a number of complementing ethical guidelines for art, culture and earth systems. The paper uses ‘ethically disturbing moments’ as an analytical tool for looking into students’ material choices in their creative processes. The four selected processes open up a personal connection to materials that results in ethical considerations during the creative practice and thus reveal the need for discussing material-focused ethics in the context of craft, design and art education. Personal aspects related to materials are discussed as embodied understanding and are seen to affect the ethics of engaging with materials.